Islamic Concept of Peace, Tolerance and Religious Harmony: An Assessment of Montgomery Watt and Robert Spencer’s views - Dr. Tariq Aziz; Dr. Hafiz Muhammad Abrar Awan; Dr. Muhammad Shahbaz Manj; Dr. Saima Munir; Dr. Taiyyiba Fatima; Dr. Navid Iqbal (Al-Qanṭara, 2022)
Abstract Islam promotes religious harmony, tolerance and peaceful co-existence not only among the Muslims, but also among the people of other faiths. As established by Islam, it is important for every Muslim to tolerate other religions, and to follow the policy of living peacefully with other nations and religions despite fundamental disagreements. However, modern western scholars and Orientalists such as Montgomery Watt and Robert Spencer are inclined to disprove all teachings of Islam while interpreting the verses of Holy Quran in their Quran commentaries and books. This article is aimed to explore how the Holy Qur'an appeals to Muslims to engage in religious tolerance, peace and harmony with the people of other religions in order to bring a true manifestation of peace and brotherhood in diversity and respect for each other's rights on the basis of their common humanity. In this article their untenable hypotheses, biased and prejudiced conclusions have been refuted. For this research, modern research methodology has been followed. Instead of paraphrasing and putting in our own words the writings and observations of various scholars, the method of Muslim historiography has been followed by quoting the writer in his own words, giving full reference to his work.